Bone age assessment: a large scale comparison of the Greulich and Pyle, and Tanner and Whitehouse (TW2) methods. Issue 2 (1st August 1999) - Bull, R K; Edwards, P D; Kemp, P M; Fry, S; Hughes, I A
Abstract : PURPOSE: Comparison of bone age assessed using either the "atlas matching" method of Greulich and Pyle or the "point scoring system" of Tanner and Whitehouse (TW2). MATERIALS AND METHODS: 362 consecutive "bone age" radiographs of the left hand and distal radius performed in a large provincial teaching hospital. Data were analysed using the "method comparison" statistical technique. Ten per cent of the radiographs were re-analysed to assess intra-observer variation. RESULTS: The 95% confidence interval for the difference between the two methods was 2.28 to −1.52 years. Intra-observer variation was greater for the Greulich and Pyle method than for the TW2 method (95% confidence limit, −2.46 to 2.18 v −1.41 to 1.43). CONCLUSION: The two methods of bone age assessment as used in clinical practice do not give equivalent estimates of bone age and we suggest that one method only (preferably the TW2) should be used when performing serial measurements on an individual patient.